Drenagem urbana e planejamento ambiental: Vale do Rio João Mendes (Niterói, RJ) - Galvão, Renata dos Santos (2010)
The theme of the research involves changes in the network of drainage in the urban environment due to the tropical urban growth, causing changes in channels with engineering works and occupation of the band marginal protection. The basin of the River John Mendes, located in the city of Niteroi, state of Rio de Janeiro, began to make changes both in the use of the soil as in the system of drainage from the 1970s, when it was intensified the occupation of the Oceanic Region, Niterói. As in most cities of tropical countries, the process of urbanization happened so disorganized, without planning. Search as general objective understanding of the dynamics of changes in the network of drainage channels of the river basin John Mendes in an attempt to provide subsidies to the planning of the area. They are specific objectives: (1) Sort use and soil cover in the basin for the years of 1976, 1996, 2001 and 2003 and that changes in the time scale affect the behavior of the network of drainage, particularly on the growth of urban areas, (2) take stock of the major engineering works carried out in the main channel over 26 years (1980 - 2005) and (3) assess the consequences of space engineering works in the sub-basins and the main channels of each one. The methodology used in the work involves the removal of the occupation of historic basin (from the 1970s), changes in the use and soil cover (in the years of 1976, 1996, 2001 and 2003) and changes in the network of drainage (1976 and 1996). Also listed were the major engineering works carried out in channels (from 1980 to 2008). Due to the large urban growth, there was an increase of the area sealed in the basin to the detriment of the areas of brejo and forest. A network of drainage has been substantially changed over 20 years, with changes in the amount and length of the channels.